"A Feeling of Space": Margaret Oliphant's Supernatural Short Fiction in Blackwood's Edinburgh Magazine. Issue 2 (3rd April 2022) - Vuohelainen, Minna
ABSTRACT: During her prolific career, the Scottish writer Margaret Oliphant (1828–97) produced a cluster of short stories and novellas about the "seen and the unseen" world of supernatural and spiritual phenomena. This essay evaluates Oliphant's contribution to the genre of the supernatural short story, focusing on the ten supernatural tales she published in the conservative Blackwood's Edinburgh Magazine between 1857 and 1897. Oliphant's stories of the seen and the unseen occupy an uneasy ideological space between the commercial, the pious and the subversive and unusually seek to establish a continuum between this life and the next. This ambivalence is represented spatially in the stories' persistent preoccupation with thresholds and journeys, which Oliphant uses to suggest the liminal encounters between the living and the dead and the passage from life to death but also to explore questions of gender, religion and modernity. Drawing on a critical framework provided by the spatial humanities, I read the stories' overlapping spatialities – generic, periodical, gendered, spiritual – as indicative of the opportunities, constraints and strategies encountered by a professional female author publishing in the ideologically charged space of the periodical press during the seminal period of transition from the Victorian to the modernist.